Carbamazepine adverse drug reactions. Issue 7 (3rd July 2018) - Fricke-Galindo, Ingrid; LLerena, Adrián; Jung-Cook, Helgi; López-López, Marisol
ABSTRACT: Introduction : Carbamazepine (CBZ) is used for the treatment of epilepsy and other neurological and psychiatric disorders. The occurrence of adverse reactions (ADRs) to CBZ can negatively impact the quality of life of patients, as well as increase health-care costs. Thus, knowledge of CBZ-induced ADRs is important to achieve safer treatment outcomes. Areas covered : This review describes the clinical features, known mechanisms, and clinical management of the main CBZ-induced ADRs. In addition, pharmacogenetic studies focused on ADRs induced by CBZ are cited. Expert commentary : CBZ-induced ADRs are well known in the literature. The metabolite CBZ-10, 11-epoxide plays an important role in the mechanism that underlies the ADRs induced by CBZ. Several factors should be considered for a safer use of CBZ, such as monotherapy prescription when possible, an adequate dose titration, knowledge of previous ADRs in the patient, and routine monitoring of CBZ plasma concentrations in symptomatic patients. Pharmacogenetics is a potential tool for CBZ therapy improvement, and the design of multicenter studies focused on the identification of biomarkers for CBZ-induced ADRs could provide useful information for a safer CBZ therapy.